Charity : the place of the poor in the Biblical tradition - Anderson, Gary A., 1955- (New Haven : Yale University Press, 2013)
In this reappraisal of charity in the biblical tradition, Anderson argues that the poor constituted the privileged place where Jews and Christians met God. He shows how charity affirms the goodness of the created order; the world was created through charity and therefore rewards it.
The challenge of charity -- Charity as an expression of faith in God. Charity as service to God -- A loan to God -- Material wealth and its deceptions -- Deliverance from death -- Is charity always rewarded? -- Charity and the goodness of creation -- Charitable deeds as storable commodities. Can merits be transferred? -- Storing good works in heaven -- Prayer, fasting, and almsgiving -- Sacrificial giving -- Deliverance from purgatory -- Conclusion: your alms are a memorial.
Includes bibliographical references and indexes.
Keywords: Charity -- Biblical teaching; Charity -- Biblical teaching